Designing a Learning Game for Elementary School Students in Learning Mathematics using a Mobile Platform - Wandri, Rizky; Setiawan, Panji Rachmat; Arta, Yudhi; Hanafiah, Anggi (Sistemasi: Jurnal Sistem Informasi, 2024)
Education is an important aspect in forming the potential of the young generation where the use of mobile platforms has become an integral part of everyday life. Over time, gadgets have become an access to learning besides books. Therefore, the increasingly complex development of the technological world encourages individuals to be able to apply technology in all their activities. Mathematics learning at elementary school level is often faced with challenges to make the learning process more fun and interactive. A common problem among students in Indonesia is that mathematics is considered a difficult subject. Monotonous learning reduces students' interest in learning. Therefore, designing learning games for elementary school students, especially in mathematics learning, can be an innovative solution to improve the quality and attractiveness of learning with interactive learning media. This research aims to create a game that allows students to learn more effectively which focuses on game development using the Game Development Life Cycle (GDLC) development model. This research produces a translation game from mathematics book learning material with the theme "Counting Numbers Up to 10,000" using the Unity 3D game engine which functions well and the application of the Game Development Life Cycle (GDLC) method also functions well.